Dexter. The second season [videorecording (DVD)] - Goldwyn, Tony; Hall, Michael C., 1971-; Benz, Julie, 1972-; Carpenter, Jennifer, 1979-; Carradine, Keith, 1949-; King, Erik; Remar, James; Lindsay, Jeffry P. (CBS DVD : [Distributed by] Paramount Home Entertainment, 2008)
Dexter is back, struggling between his love for killing and his job in the homicide department.